“Clozapine & Valbenazine for Treatment of Tardive Cervical Dystonia: A Case Report”: Tardive Cervical Dystonia (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Cervical dystonia is a subtype of tardive dyskinesia characterized by smooth, sustained muscle contractions affecting the head, neck, and shoulders. This condition can be caused by antipsychotic medication exposure. It has a significant impact on the patient’s quality of life and represents a treatment challenge for providers. We present the case of a 26-year-old male with a history of schizophrenia treated with antipsychotic medications who presented with on and off smooth twisting movements of his neck and hand tremors. He was initially treated with benztropine and a decrease in the dose of his antipsychotic medications. However, when his symptoms continued to worsen, he was cross tapered to clozapine and valbenazine. Valbenazine is a VMAT2 inhibitor FDA approved for treatment of tardive dyskinesia, but there is little data regarding its use for tardive dystonia. The cervical dystonia impact profile-58 (CDIP-58) was administered to monitor the patient’s symptoms. Overall, there was a reduction in cervical dystonia symptoms within a 10-week period. This case illustrates the potential for clozapine plus valbenazine to treat tardive cervical dystonia.
Keywords: Dystonia; antipsychotics; schizophrenia